PP77 Changes Ahead – Again! Lessons Learned from a Study Exploring Receptivity to Policy Changes in NHS Commissioning. (10th September 2013) - McCafferty, S; Bate, A; Finch, T; McGovern, T
Abstract : Background: In the National Health Service (NHS) in England commissioning is the process of prioritising resources to ensure that health and care services are provided effectively to meet the needs of the population. Commissioning policy has been subject to extensive tremendous reforms and recent years have witnessed the introduction and termination of the 'World Class Commissioning' (WCC) initiative, the White Paper 'Equity and Excellence: Liberating the NHS' and the subsequent transfer of commissioning responsibility from primary care trusts (PCTs) to clinical commissioning groups (CCGs). The impact of these reforms and how receptive organisations are to these policy changes is not fully understood. This research utilised the opportunity of the changing policy landscape as a natural experiment to explore the receptivity of a commissioning organisation to these changes. Methods: A case study approach was adopted within one PCT following its evolution to CCG. A series of in-depth interviews were conducted across three time points (n = 11, total 34), to understand organisational responses to changes in commissioning policy. Thematic analysis and a constant comparative approach were used to identify themes. Results: This research identified the key factors influencing the organisation's ability to deliver policy objectives, in terms of key relationships structures and processes. Four key factors were identified. These were: policy, change agenda and locale, culture, and system management. Sub themes within these factors were also identified, particularly of note were: the level of commitment generated through the policy, the clarity of goals, historical working practices and perceptions of power. Conclusion: These results have significant implications for emerging CCGs and provide guidance for future policy development. Previous commissioning policy initiatives have failed to adequately manage and address issues within the broader NHS system. Further continual reorganisation was found to be particularly disruptive. Results suggest that commissioning organisations are likely to be more receptive to future commissioning policies which are coherent, feasible and generate buy-in from key stakeholders. During this time of extended policy change transitions need to be carefully managed to avoid loss of valuable expertise.